2017
DOI: 10.1038/s41598-017-08598-3
|View full text |Cite
|
Sign up to set email alerts
|

Optical µ-Printing of Cellular-Scale Microscaffold Arrays for 3D Cell Culture

Abstract: Guiding cell culture via engineering extracellular microenvironment has attracted tremendous attention due to its appealing potentials in the repair, maintenance, and development of tissues or even whole organs. However, conventional biofabrication technologies are usually less productive in fabricating microscale three-dimensional (3D) constructs because of the strident requirements in processing precision and complexity. Here we present an optical µ-printing technology to rapidly fabricate 3D microscaffold a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 46 publications
0
30
0
1
Order By: Relevance
“…An in-house optical exposure setup, as shown in Figure 2 a, was used to fabricate the optical fiber-tip sensors. The setup consists of a high-power UV source (365 nm), a UV-grade digital mirror device (DMD) for generation of optical patterns, projection optics for scaling down optical images, and a digital camera for machine vision metrology [ 28 , 29 , 30 ]. As it is a vitally important step to deposit uniform thin layers of SU-8, an ultrasonic nozzle was utilized to integrate the spray coating process with the optical maskless exposure technology to establish an optical 3D μ-printing technology.…”
Section: Methodsmentioning
confidence: 99%
“…An in-house optical exposure setup, as shown in Figure 2 a, was used to fabricate the optical fiber-tip sensors. The setup consists of a high-power UV source (365 nm), a UV-grade digital mirror device (DMD) for generation of optical patterns, projection optics for scaling down optical images, and a digital camera for machine vision metrology [ 28 , 29 , 30 ]. As it is a vitally important step to deposit uniform thin layers of SU-8, an ultrasonic nozzle was utilized to integrate the spray coating process with the optical maskless exposure technology to establish an optical 3D μ-printing technology.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that specific scaffold architectures achieved by the 3D bioprinting technique resulted in optimal murine follicle survival and differentiation in vitro. Xia et al [ 62 ] fabricated arrays of 3D cubic microscaffolds with cubical size matching the single-cell size using a polymer material via a vat photopolymerization process ( Figure 6 b). As shown in Figure 6 c–f, GelMA was in situ printed on the microscaffold.…”
Section: Biomaterials For Next-generation Bioprintingmentioning
confidence: 99%
“…Inset: Magnification of scaffold porosity, reprinted from [ 61 ] with the permission of Nature Publishing Group, Copyright 2017; ( b ) SEM images of 3D cubic microscaffolds via vat photopolymerization process. ( c , d ) SEM images of the cubic microscaffolds with in situ printed GelMA (blue); ( e , f ) the fluorescent staining of f-actin (red) and nuclei (blue) of the human mesenchymal stem cells (hMSCs) cultured in the corresponding microscaffolds (gelation shown as the dashed area), reprinted from [ 62 ] with the permission of Nature Publishing Group, Copyright 2017; ( g ) Photographs of the bioprinted agarose templates (green); ( h ) Respective microchannels perfused with a fluorescent microbead suspension (pink, diameter of microchannels: 500 μm), reprinted from [ 63 ] with the permission of Royal Society of Chemistry, Copyright 2014. ( i ) Scheme of 3D bioprinting of the polypeptide–DNA hydrogel, reprinted from [ 66 ] with the permission of John Wiley and Sons, Copyright 2017; ( j , k ) SEM images of hybrid structure of cartilage decellularized extracellular matrix (cdECM) with PCL framework; ( l , m ) microscopic images of cell-printed structure of adipose decellularized extracellular matrix (adECM) with PCL framework, reprinted from [ 69 ] with the permission of Nature Publishing Group, Copyright 2014; ( n ) Schematic of coaxial nozzle-assisted electrohydrodynamic cell printing, reprinted from [ 73 ] with the permission of WHIOCE publishing, Copyright 2017.…”
Section: Figurementioning
confidence: 99%
“…top-lensed microlenses (TLMLs). With an in-house DMD-based optical μ-printing platform [20,21], the relation between the exposure dose of UV light and the cured depth of photopolymer is studied. Then, a dynamic exposure scheme using the bitmap of corrected exposure doses is developed to facilely tailor the profiles of microlenses pixel by pixel and thereby precisely print arrays of top-lensed microlenses with either elongated depth of focus or dual foci.…”
Section: Introductionmentioning
confidence: 99%
“…1(d) that two separate foci with the distance of 215 μm was achieved. The optical μ-printing setup consists of a high-power UV light source (OmniCure 2000 System, Lumen Dynamic Group Inc.), a DMD (DLi4120 0.7" XGA, Texas Instruments, USA), projection optics, and a high-precision motorized X-Y stage (M-687, Physik Instrumente GmbH & Co.) [20,21]. The motorized stage can enable the precise location of exposure for fabrication of large-area microstructures through seamless pattern-stitching process.…”
Section: Introductionmentioning
confidence: 99%